Efectos del parasitismo sobre el tejido branquial en peces cultivados: estudio parasitologico e histopatologico - Martins, Maurício Laterça [UNESP]; Romero, Nicolás Garcia (Sociedade Brasileira de Zoologia, 1996)
One hundred four out of 225 diagnosticated cases were myxosporidian, monogenean, Ichthyophthirius multifiliis Fouquet, 1876 and bacterial diseases in Piaractus mesopotamicus Holmberg, 1887 (pacu), Colossoma macropomum Cuvier, 1818 (tambaqui) and tambacu, at Aquaculture Center, Universidade Estadual Paulista (UNESP), Jaboticabal, São Paulo, Brazil, between 1992 and 1995. The gills were fixed in 10% buffered formalin solution to posterior histologic routine. It was observed Henneguya sp. cysts into the capillaries of the secondary lamellae, encapsulated by the respiratory epithelium cells. It provoked adherence of the adjacent lamellae, hyperplasia, congestion, oedema and epithelium displacement. Monogeneans infestations by Anacanthorus penilabiatus Boeger, Husak & Martins, 1995 and Ancyrocephalinae sub-family caused light inflammatory reaction and hyperplasia. In severe infestations was observed hyperplasia of primary lamellae, necrosis, oedema, respiratory epithelium displacement, ruptured pillar cells and telangiectasis. Response to I. multifiliis was limited to surrounding epithelial cells in young fishes and hyperplasia, necrosis, inflammatory infiltrate and oedema in old fishes. Such lesions iniciate hyperplasic and oedematous process that with inflammation of the parasitic sites, provoked alterations over gases and ions interchange surface and consequently fish metabolism.
Effect of the parasitism on the gill tissue of cultivated fishes: parasitological and histopathological studies
Keywords: Protozoa; Monogenea; histopathology; Brazilian fish